2020
DOI: 10.1088/1361-6560/ab82e7
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo and water calorimetric determination of kilovoltage beam radiotherapy ionization chamber correction factors

Abstract: The in-phantom calibration method for radiotherapy kilovoltage x-ray beams requires ionization chamber correction factors. The overall ionization chamber correction factor accounts for changes in the chamber response due to the displacement of water by the chamber cavity and wall, the presence of the stem and the change in incident photon energy and angular distribution in the phantom to that in air. A waterproof sheath, if required, is accounted for in a sheath correction factor. The aim of this study is to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
(37 reference statements)
2
8
0
Order By: Relevance
“…Equation ( 5) is also based on the assumption, that the chamber readings M w,Q and M a,Q can be replaced by the dose values D det,w,Q and D det,a,Q . In a recent study Bancheri et al (2020) have shown, that the ratios of the correction factors (k w k ii ) w,Q / (k w k ii ) a,Q are indeed unity for spectra in the same energy range as investigated here, i.e. the impact of the correction k w • k ii on the perturbation correction p Q is also negligible.…”
Section: Air-kerma Based Formalismsupporting
confidence: 63%
See 2 more Smart Citations
“…Equation ( 5) is also based on the assumption, that the chamber readings M w,Q and M a,Q can be replaced by the dose values D det,w,Q and D det,a,Q . In a recent study Bancheri et al (2020) have shown, that the ratios of the correction factors (k w k ii ) w,Q / (k w k ii ) a,Q are indeed unity for spectra in the same energy range as investigated here, i.e. the impact of the correction k w • k ii on the perturbation correction p Q is also negligible.…”
Section: Air-kerma Based Formalismsupporting
confidence: 63%
“…The agreement of both data sets is within 0.2%, whereat the data using the egs_kerma user code seem to be systematically higher. Additionally, the data from the TG-61 protocol and new data from the publication of Bancheri et al (2020) are included. Bancheri also used the EGSnrc system applying the FLURZnrc and g user code.…”
Section: X-ray Spectra and Mass Energy Absorption Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values for overall chamber correction factors and water‐to‐air mass energy absorption coefficient ratios are now two decades old, and the uncertainties associated with them are high, as shown in Table V. Bancheri et al 42,47 recently reported the calculation of these correction factors for different ionization chamber models, including the NE2571 model, using MC simulation. They reported inconsistencies between the measured and calculated absorbed dose to water‐to‐air kerma ratio, indicating the need for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, kilovoltage dosimetry is so important, the IAEA provides two separate sections in the TRS398 Code of Practice for both low and medium energy X-rays while the megavoltage X-ray beam dosimetry recommendations are contained within one section [17]. In addition, primary standard dosimetry laboratories around the world continue to maintain and develop their standards for kilovoltage X-ray beams [18,19].…”
Section: Opening Statementmentioning
confidence: 99%